Frequency of the Factors Leading to Postmenopausal Bleeding - Pari Imam Gul, Asim Iqbal Qureshi, Uzma Khalid, Maria Khan, Tahreem Rasheed, Syeda Sahar Zahra, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: Aim of this study is to evaluate the frequency of factors underlying postmenopausal bleeding in local population. Study design: A cross sectional study Duration and place: Department of obstetrics and gynecology of Bakhtawar Amin Trust Hospital Multan from 14th April 2019 to 14th April 2020. Methodology: The study included 130 patients who fulfilled inclusion criteria. Demographic data including period of complain and age was collected. Cervical smears of all subjects were taken and investigated. Transvaginal ultrasonography of all patients were also done. SPSS-IBM version 20 was used used to analyze data.P value 50.05 was considered statistically significant. Results: Atrophic endometrium was seen in 46.2% patients, Endometritis 18.5%, Endometrial hyperplasia 10%, Endometrial carcinoma 5.4%, Cervical cancer 7.7% and Polyp was 10.8%. Conclusion: It can be concluded that only the most frequent cause of PBM in post menopausal women was found similar to previous data, all other causes had different ranking.